Avaliação da utilidade de um software de simulação cromatográfica na separação de Flavonóides por CLAE-DAD de fase reversa - Figueiredo Junior, José Wilson (2008)
High Performance Liquid Chromatography (HPLC) allows both qualitative and quantitative chemical analysis, separating and identifying substances in mixtures with speed and efficiency. However, factors governing chromatographic retention are complex and the method development phase consumes a lot of resources. In our work we evaluated a chromatographic simulation software package (HIPAC-G, HIPAC-B e HIPAC-S, Phenomenex, Torrance, USA) for optimizing the chromatographic separation of eight flavonoid standards (3-O-[β-Dglucopyranosyl-( 1→6)-α-L-ramnopyranosyl]-7-O-α-L-ramnopyranosyl kampferol; hesperidine; kampferol; tiliroside; quercetin; 3,4 ,7,8-tetra-O-methyl-gossypetine; 3,3 ,4 ,7,8-penta-O-methylgossypetine and 3,3 ,4 ,7-tetra-O-methyl-quercetin). The HIPAC model of retention is based on the known linear relationship that exists between the retention factor of an analyte and the percentage of organic solvent in the mobile phase, to simulate retention data. Using gradient elution, three trial runs were done (preliminary runs that are used to input retention data to the software). The first trial run used a C18 column (250 x 4,6 mm, 5 m) and as mobile phase a gradient from 5 to 95% of acetonitrile (solvent B) in 0,1% formic acid (solvent A) at a flow rate of 1 mL/min with UV detection at 264 nm. The first trial run was comprised of two gradient runs using the same chromatographic conditions but different gradient duration times (30 and 60 minutes respectively). The second trial run used the same chromatographic conditions as the first one, but methanol instead of acetonitrile as the organic modifier and 10% and 100% as the initial and final %B, respectively. The third trial run was done with the same chromatographic conditions as the second one, but using a column with different stationary phase and dimensions (C8, 150 x 4,6 mm, 5 m). The retention data of the three trial runs were used as input to the simulation software, using the HIPAC-G module. For isocratic mode simulation using the HIPAC-B module, both a C8 (150 x 4,6 mm, 5 m) and a C18 (250 x 4,6 mm 5 m) column was used with binary mixtures of MeOH (solvent B) in 0,1% formic acid (solvent A). Two trial runs with 60% and 70%B were done for each column and the resulting retention data used as input for simulation. The optimized separation conditions as suggested by HIPAC-B were used as input for HIPAC-S to optimize the system chromatographic conditions. The optimization criterion used for all simulations was the average global resolution for all peaks in the chromatogram. Altogether twelve simulations in gradient elution mode and four isocratic simulations were done. The simulated retention data was then confronted with experimentally obtained retention data for the eight flavonoid standards. The correlation coefficient (r2) between simulated and observed retention times for the analytes when eluted in gradient mode varied from 0,9416 to 0,9992 (n=12). The correlation coefficient in isocratic mode varied from 0.9999 to 1 (n=4), indicating an excellent efficiency in predicting retention data for the mixture tested. Taken together our results show that the use of chromatographic simulation software such as HIPAC-G, HIPAC-B e HIPACS can constitute an important tool in the optimization of separation conditions of complex mixtures, such as those found in the field of natural products.